Cellular uptake and targeting of low dispersity, dual emissive, segmented block copolymer nanofibers - Street, Steven T. G; He, Yunxiang; Jin, Xu-Hui; Hodgson, Lorna; Verkade, Paul; Manners, Ian (Chemical science (Cambridge), 2020)
Polymer-based nanoparticles show substantial promise in the treatment and diagnosis of cancer and other diseases. Herein we report an exploration of the cellular uptake of tailored, low dispersity segmented 1D nanoparticles which were prepared from an amphiphilic block copolymer, poly(dihexylfluorene)- b -poly(ethyleneglycol) (PDHF 13 - b -PEG 227 ), with a crystallizable PDHF core-forming block and a 'stealth' PEG corona-forming block with different end-group functionalities. Segmented C-B-A-B-C pentablock 1D nanofibers with varied spatially-defined coronal chemistries and a selected length (95 nm) were prepared using the living crystallization-driven self-assembly (CDSA) seeded-growth method. As the blue fluorescence of PDHF is often subject to environment-related quenching, a far-red BODIPY (BD) fluorophore was attached to the PEG end-group of the coronal B segments to provide additional tracking capability. Folic acid (FA) was also incorporated as a targeting group in the terminal C segments. These dual-emissive pentablock nanofibers exhibited uptake into >97% of folate receptor positive HeLa cells by flow cytometry. In the absence of FA, no significant uptake was detected and nanofibers with either FA or BD coronal groups showed no significant toxicity. Correlative light and electron microscopy (CLEM) studies revealed receptor-mediated endocytosis as an uptake pathway, with subsequent localization to the perinuclear region. A significant proportion of the nanofibers also appeared to interact with the cell membrane in an end-on fashion, which was coupled with fluorescence quenching of the PDHF core. These results provide new insights into the cellular uptake of polymer-based nanofibers and suggest their potential use in targeted therapies and diagnostics. The cellular uptake of tailored, modular, and segmented low dispersity nanofibers with a crystalline π-conjugated core has been studied.